Guided Inquiry Worksheets with Teaching Aids: Improving Students’ Scientific Literacy - Utami, Vina Bekti; Fitriani, Wulandari; Suhendar, Haris (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
This study aims to improve students' scientific literacy through the use of worksheet integrated with guided inquiry aided by teaching aids. This study used a Pre-Experimental design with a One-Group Pretest-posttest design conducted in 1 class. The subjects of the study were students of Phase D of MTSS Persis Cikalongkulon. Data collection techniques were pre-test and post-test (scientific literacy) and questionnaires. Worksheet-guided inquiry aided by teaching aids was declared very feasible by expert validators and practitioners (science teachers) and effective in improving students' scientific literacy with an N-Gain of 0.51 which is included in the moderate category. The practicality of worksheet has an average score of 35.87 out of a maximum total score of 48 and these results are in the good category. Based on the questionnaire of students' interest in learning, the results showed that 80% of students felt the learning atmosphere was more active and enjoyable.